SYSTEMATIC LITERATURE REVIEW: IMPLEMENTASI CULTURO-TECHNO-CONTEXTUAL APPROACH DALAM PEMBELAJARAN IPA DI SEKOLAH DASAR - Megawati; Yantoro (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
Culturo-Techno-Contextual Approach (CTCA) is a new approach in science learning. CTCA integrates three main pillars: culture, technology and context, to create meaningful and relevant learning experiences for students. This research is a systematic review of 9 scopus and WoS indexed articles related to CTCA in science learning in 2019-2024. It addresses questions about the suitability of its application at the primary school level, as well as practical steps to implement it. Although CTCA has been widely applied at the upper secondary level, this research shows that the approach is also highly relevant for education in primary schools, where integrating local wisdom and technology can improve students' understanding of science materials. The findings highlight the importance of adapting learning methods that are responsive to students' needs and context, as well as the need for better introduction of technology in the learning process.